COMMUNAL ECONOMY TARIFF POLICY - K. A. Ivanov (Модернизация, инновация, развитие, 2016)
Approach to management of apartment houses in Russia is close to that practiced in developed foreign countries. Main difference consists in that market relations are completely operable there. Particularly, it is possible to transfer dwelling funds from one managing company to another oneas well as easily, within a couple of days, to change supplier of a communal service. At the same time, the population is provided with communal services under strict control on the part of state authorities who determine competing private enterprises’ work rules, protect consumers’ rightsand guarantee quality standards for vital services.